Management Strategies to Reduce User Switching Behavior: Analyzing Critical Factors in Augmented Reality Technology Usage in E-commerce - Kembau, Agung Stefanus; Malae, Friscilla Elsyabeth; Lendo, Fresi Beatrix (Universitas Bunda Mulia, 2024)
This study investigates the factors influencing the switching behavior of Augmented Reality (AR) technology users in e-commerce in Indonesia, employing the Push-Pull-Mooring (PPM) framework. Data were gathered from 178 respondents experienced in using AR applications in e-commerce between February and April 2024. Structural Equation Modeling (SEM) analysis revealed that Dissatisfaction, Poor User Experience (UX), Attractiveness of Alternatives, Innovative Features, and Social Influence positively and significantly affect Switching Behavior, whereas Switching Costs significantly inhibit it. The model accounts for 64% of the variability in user switching behavior. These findings highlight that e-commerce platforms must prioritize enhancing user experience quality, addressing dissatisfaction, and introducing innovative features to retain users. Additionally, managing switching costs is crucial to reducing barriers to user switching behavior. By focusing on these areas, e-commerce platforms can develop more effective strategies to improve user retention and satisfaction. Future research should broaden the scope by incorporating additional variables, conducting longitudinal studies, and exploring AR technology's impact across various industries. These insights provide valuable guidance for e-commerce management in optimizing their platforms to meet user needs and preferences.